The Effect of Applying Talking Stick Type Learning Model in Mufrodat Learning: Quasi Experimental Research on Junior High School - Ihda Filzafatin Habibah; Munirul Abidin (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This study aims to determine the effect of the application of the